The Position of Children Born from Keris Marriages in Balinese Customary Law Inheritance - FEBRIANA, Ni Kadek; SUJANA, I Nyoman; SETYAWATI, Ni Komang Arini (Indonesia Strategic Sustainability, 2024)
Purpose: The existence of Keri's Marriage impacts the child who is born, where the child's position in terms of inheritance is questionable. It happens because first, the child who is born does not have a father who is responsible for his actions, so the mother of the child must carry out the keris marriage procession or second, the child gets recognition from his father and only during the marriage procession is his father symbolized by a keris because of his inability to attend the marriage procession or third, the child who is born carries out a peperasa or adoption ceremony.Methodology:In this study, the author uses an empirical legal research method using a statutory approach, a legal sociological approach and a case approach. Two types of data are used in empirical legal research: primary and secondary. Data collection for the preparation of this study was carried out in a village in Tabanan Regency. Findings: The research findings explain the results of research data processing, which do not include numbers but explain in detail the results carried out between research variables. They also explain the implications of research where research has a direct impact.Implication:In the case that occurred in Pandak Gede Village, the marriage procession was continued again after the arrival of the male party, so the child was administratively recognized by his biological father. In terms of inheritance, the child had the right to inherit because he received recognition from his biological father.